Bertolaklah Ke Tempat Lebih Dalam Menuju Paroki Definitif - Angela Florida Mau; Stanislaus Digman Layan (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
The Lauran Sacred Heart Quasi-Parish has held its first pastoral deliberation. This activity aims to provide an understanding of the direction of the pastoral vision of the Diocese of Amboina, reflect on the faith of the participants, and produce plans and recommendations for forming a definitive parish. This research is descriptive qualitative research carried out using the literature study method. The aim of the research is to provide an overview of church independence in relation to the pastoral vision of the Diocese of Amboina. The research results show that there is a relationship between the idea of ​​establishing a definitive parish and the pastoral vision of the Amboina Diocese. It is hoped that this research will provide positive implications in preparing the design and recommendations for the Lauran Sacred Heart quasi-parish to become a definitive parish.